2008
DOI: 10.1038/cgt.2008.58
|View full text |Cite
|
Sign up to set email alerts
|

REIC/Dkk-3 overexpression downregulates P-glycoprotein in multidrug-resistant MCF7/ADR cells and induces apoptosis in breast cancer

Abstract: The overexpression of reduced expression in immortalized cells (REIC)/Dickkopf-3 (Dkk-3), a tumor suppressor gene, induced apoptosis in human prostatic and testicular cancer cells. The aim of this study is to examine the potential of REIC/Dkk-3 as a therapeutic target against breast cancer. First, the in vitro apoptotic effect of Ad-REIC treatment was investigated in breast cancer cell lines and the adenovirus-mediated overexpression of REIC/Dkk-3 was thus found to lead to apoptotic cell death in a c-Jun-NH 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 34 publications
6
110
1
Order By: Relevance
“…The suppression of tumor growth was further confirmed in an in vivo situation using an orthotopic tumor model. These phenomena were consistent with other published studies (3,5,9,10,(15)(16)(17)(18), showing that ectopic expression of REIC/ Dkk-3 induces apoptosis and inhibits cell proliferation in various cancer cells. Therefore, the lack or absence of endogenous REIC/Dkk-3 expression in RM9 cancer cells seems to be important for the cellular effects induced by the REIC/Dkk-3 overexpression.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The suppression of tumor growth was further confirmed in an in vivo situation using an orthotopic tumor model. These phenomena were consistent with other published studies (3,5,9,10,(15)(16)(17)(18), showing that ectopic expression of REIC/ Dkk-3 induces apoptosis and inhibits cell proliferation in various cancer cells. Therefore, the lack or absence of endogenous REIC/Dkk-3 expression in RM9 cancer cells seems to be important for the cellular effects induced by the REIC/Dkk-3 overexpression.…”
Section: Discussionsupporting
confidence: 82%
“…REIC/Dkk-3 expression is down-regulated in a broad range of cancer cell lines and clinical cancer materials (2)(3)(4)(5)(6)(7)(8)(9)(10). The expression of the human REIC/Dkk-3 gene is significantly down-regulated in human prostate cancer specimens in comparison to normal human prostate tissue at the protein level (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of apoptosis was demonstrated to be selective, i.e., efficient killing of cancer cells with only a marginal effect on normal counterparts (2). In addition, Ad-REIC reversed resistance of cancer cells to anti-cancer drugs via down-regulation of P-glycoprotein (9). Furthermore, we recently showed that Ad-REIC has an indirect host-mediated anti-tumor activity in vivo by the induction of IL-7 (10).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, REIC was designated as REIC/Dkk-3. Previous studies by our group have demonstrated that overexpression of REIC/Dkk-3 by an adenovirus (Ad)-REIC vector resulted in a therapeutic effect against numerous human cancer subtypes via a mechanism triggered by endoplasmic reticulum (ER) stress-mediated c-Jun N-terminal kinase (JNK) activation (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%